Cost-efficient method for unsymmetrical meso-aryl porphyrins and iron oxide-porphyrin hybrids prepared thereof. Issue 41 (20th September 2016) - Henriques, César A.; Pinto, Sara M. A.; Pina, João; Serpa, Carlos; Fernandes, Auguste; Rossi, Liane M.; Ribeiro, M. Filipa; Pereira, Mariette M.; Calvete, Mário J. F.
Abstract : Synthesis, characterisation and photophysical properties of magnetic iron oxide-porphyrin hybrids starting from unsymmetrical porphyrins, which are prepared by a cost-efficient methodology. Abstract : Herein, the synthesis and characterisation of magnetic iron oxide-porphyrin hybrids, constituted of iron–oxide magnetic nanoparticles covalently linked to an unsymmetrically substituted meso -aryl porphyrin, are described. The methodology features for the preparation of the key unsymmetrically substituted meso -aryl porphyrin synthons are discussed, with emphasis on sustainability and in economical terms. The "NaY method" herein reported allows large scale and economical preparation, which are demonstrated by its reusability and at least two-fold yields, when compared with classical porphyrin synthetic methods and also presents a much better cost-efficiency rationale and lower environmental impact. Upon covalent linking to iron–oxide magnetic nanoparticles, the new hybrids are fully characterised by thermogravimetry/differential scanning calorimetry, transmission electron microscopy and infrared spectroscopy and their photophysical properties were measured, which demonstrate that the presence of the magnetic nanoparticle counterparts does not affect these properties, thus allowing the materials to keep the photophysical features imparted by their porphyrin counterparts.